On Information Hiding System With Multiple Messages - Haroutunian, Mariam E.; Tonoyan, Smbat A . (Mathematical Problems of Computer Science, 2021)
Many algorithms and schemes of multiple watermarking, fingerprinting and multimedia data creation are implementing to hide more than one watermark. Information theoretical analysis of information hiding system with multiple messages is considered in this paper. The rate-reliability-distortion function (which we call the information hiding E-capacity [5, 9]) for this system, in case of two messages (watermarks) is investigated. The inner bounds for information hiding E-capacity and for information hiding capacity [1] regions are constructed.